Tropical bed bug (Cimex hemipterus) in Malaysia: survey on pest control operators management and control strategies (hemiptera:cimicidae) - Zulaikha Z.,; A. H. A. Majid, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Bed bugs cases have been at alarming rate in most foreign countries compared to Southeast Asia, especially in Malaysia. Lack of morphological understanding and ways to control among the society and professionals have become factors of their resurgence. An online survey was conducted among Pest Control Operators (PCO) from different pest control companies in nine states of Malaysia to investigate the commonly used technique in treating bed bugs. The forms were distributed via online to all pest control companies but only 48 of them have responded. Other preferences such astype of premises, number of cases, number of successful treatment and resistance in bed bugs after residual treatment were also included in the questionnaires. It was found that most Pest Control companies preferred chemical and spray method for treatment (66.7%) especially in Kuala Lumpur and Selangor which also had the highest infestation of bed bugs in their premises such as hotels, motels and residential houses. Most companies prefer RM500-1000 as charging cost per treatment site. Although professionals hardly find resistance bed bugs in their treatment cases (75%), the number of complete eradication per site has been very low (41.7%). Therefore, improvements in treating bed bugs should be investigated in details to prevent widespread of bed bugs throughout Malaysia.